Development of rotor flux control laws for high-speed asynchronous electric drive - M. V. Glazyrin; I. A. Aleinikov (Омский научный вестник)
The article analyzes the overload capacity of asynchronous variable frequency drives with orientation on the rotor flux linkage vector at rotational speeds higher than nominal. Marked and mathematically taken into account factors limiting the magnitude of the motive electromagnetic moment of an asynchronous electric drive in the entire range of values of shaft speed. The division of this region of values into three working zones is substantiated, for each of which there is defined its own individual law of formation of the driving force modulo of the resulting rotor flux-coupling vector.